Quality Control Analysis To Reduce Bag Product Defects Using The Lean Six Sigma Method (Case Study: Alfajar Bag Convection Msmes, Jakarta) - M. Syahril; Azriadi, Emon; Tanjung, Lailatul Syifa (Journal of Engineering Science and Technology Management (JES-TM), 2024)
The background of this research is to control the quality of bag production to reduce product defects and improve the quality of the resulting products. The purpose of this research is to identify the causes of product defects, determine the DPMO and sigma values, and propose improvements using the Lean Six Sigma method for bag production at Alfajar Bag convection. This research is both descriptive quantitative and qualitative, collecting production data over one year from May 2022 to April 2023. It was found that 11,940 Rempel Backpacks were produced, with 1,147 defective items, resulting in an average defect rate of 9.6%. The research analysis uses the Lean Six Sigma method to understand quality control through several stages. In the Define phase, four types of Critical To Quality (CTQ) attributes were identified for Rempel Backpack production. In the Measure phase, the calculations for DPMO and Sigma Level revealed an average DPMO of 24,015.913 and a Sigma Level of 3.477ϭ. In the Analyze phase, five main factors and seven types of waste affecting production were identified. In the Improve phase, several improvement suggestions were made to reduce product defects and waste in the bag production at Alfajar Bag. In the Control phase, the improvement suggestions analyzed in the Improve phase were implemented, and continuous monitoring and improvements were carried out.